RNA modifications and their role in gene expression - Artika, I. Made; Arianti, Rini; Demény, Máté Á.; Kristóf, Endre (Frontiers in Molecular Biosciences, 2025)
Post-transcriptional RNA modifications have recently emerged as critical regulators of gene expression programs. Understanding normal tissue development and disease susceptibility requires knowledge of the various cellular mechanisms which control gene expression in multicellular organisms. Research into how different RNA modifications such as in N6-methyladenosine (m6A), inosine (I), 5-methylcytosine (m5C), pseudouridine (Ψ), 5-hydroxymethylcytosine (hm5C), N1-methyladenosine (m1A), N6,2′-O-dimethyladenosine (m6Am), 2′-O-methylation (Nm), N7-methylguanosine (m7G) etc. affect the expression of genes could be valuable. This review highlights the current understanding of RNA modification, methods used to study RNA modification, types of RNA modification, and molecular mechanisms underlying RNA modification. The role of RNA modification in modulating gene expression in both physiological and diseased states is discussed. The potential applications of RNA modification in therapeutic development are elucidated.